Design of a low-profile slot antenna array - Htet Aung, Than (2018)
Microstrip fed slot antenna are typically low profile and high conformability, and hence they are favorable for airborne applications and satellite communications. The main disadvantage of slot antenna is their bi-directional radiation pattern. This characteristic can be eliminated when the slot antenna is backed by cavity. In this project, cavity-backed slot antenna and the dimensions of the antenna which affects the antenna performance are examined. The cavity-backed slot antenna which previously designed by other scholars has been modified by adding in additional slot and main objective is to improve the gain of the antenna. Countless repetitions of simulate -accesssimulate were done to achieve project objective. Important milestones and lesson learnt during the process were recorded and discuss in this report. At the end of this project, finalized improved design of cavity-backed slot antenna will be presented. The design will be fabricated and measurement will be done to verify the simulation result.